Systematic metabolic engineering of Yarrowia lipolytica for efficient production of phytohormone abscisic acid - Mei-Li Sun; Ziyun Zou; Lu Lin; Rodrigo Ledesma-Amaro; Kaifeng Wang; Xiao-Jun Ji (Synthetic and Systems Biotechnology)
Abscisic acid (ABA) is an important phytohormone with diverse applications. It currently relies on the fermentation of Botrytis cinerea, which suffers from limited availability of genetic engineering tools. Here, Yarrowia lipolytica was engineered to enable de novo biosynthesis of ABA. To overcome the rate-limiting P450 enzymes, systematic engineering strategies were implemented. Firstly, the dissolved oxygen was increased to boost the activity of P450 enzymes. Secondly, the expansion of endoplasmic reticulum was implemented to improve the functional expression of P450 enzymes. Lastly, rate-limiting enzymes were assembled to facilitate substrate trafficking. Moreover, ABA production was further improved by strengthening the mevalonate pathway. Finally, the engineered strain produced 1221.45 mg/L of ABA in a 5-L bioreactor. The study provides effective approaches for alleviating rate-limiting P450 enzymes to enhance ABA production and achieve competitive industrial-level ABA production in Y. lipolytica.